Pengaruh Penyajian Laporan Keuangan dan Aksesibilitas terhadap Akuntabilitas Pengelolaan Keuangan Daerah - Hilyati Nurul Shadrina; Sjarief Hidajat (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this research is to test and prove the relationship between the variables of financial statement presentation and accessibility to the accountability variables of regional financial management in Tuban Regency. This research uses quantitative methods. The government of Tuban Regency is the place of this research. Purposive sampling was used in this study, and distributing questionnaires to respondents was the data collection method used in this study. The SPSS 26 software application is used for data analysis techniques in this study. This study found that the regional financial management accountability variable was influenced by the presentation of financial reports, but accessibility had no effect on regional financial management accountability. Presentation of financial reports that are complete and in accordance with SAP allows control and supervision of proper financial management. The accessibility of regional financial reports does not affect the accountability of regional financial management. This may be because there are still many obstacles to obtaining local government financial reports. In addition, both the mass media and websites do not provide much information regarding local government financial reports in each region.